EFFECTIVE METHODS OF USING WORKING CAPITAL IN THE PROCESS OF PHYSICAL EDUCATION OF STUDENTS - Maxmudov Sharofiddin Renasans; Maxmudova Madina (Journals Park Publishing, 2023)
In this paper, the transition from Group approaches in the physical education of students and students at the present stage of Education to personality-oriented teaching and training methods based on the individual capabilities and abilities of the students will help to improve the state of Health. and increase physical training. In the practice of physical education, this method is the method of circulating exercise. The effectiveness of such an organization is such that the intensity of the classes increases significantly, because all students train at the same time and at the same time independently, in proportion to their capabilities and efforts.
Keywords: student; exercises of turnover; education-training, training, Sports, Physical Education, Social Value, ability to move, pedagogy, pupils, students.